If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15(h + -2) = 0 Reorder the terms: -15(-2 + h) = 0 (-2 * -15 + h * -15) = 0 (30 + -15h) = 0 Solving 30 + -15h = 0 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + -15h = 0 + -30 Combine like terms: 30 + -30 = 0 0 + -15h = 0 + -30 -15h = 0 + -30 Combine like terms: 0 + -30 = -30 -15h = -30 Divide each side by '-15'. h = 2 Simplifying h = 2
| 5x+3+3x=9x+3-x | | 2.95x+5.95(90-x)=405 | | -t+4=873 | | -t+4= | | 4-5+x-(-1)=5 | | -2+4x=-23 | | 5x^2y^2+9xy-2=0 | | 12x^3-13xy-14y^2=0 | | 8-2(2x+1)=3(x-5) | | 10+(9+(-7))= | | 14-8=e | | -.3(.7x-.9)=-1.83 | | 12*p=3 | | 2.3x-9=1.2 | | 24x=40 | | m+-6+-1=-9 | | 12x+376=280+15x | | 25h-50=250 | | x-(-5)+2=9 | | 3(3y+3)-7y=15 | | (2/3)-(2w+2/5)=2-(w+16/6) | | 9-7(x-1)=3(x-3)-5(x+3) | | 4b-7=10+b | | x*2-12=-3+x | | 5(6-3u)=-4u-12 | | 9x^2-48=-12x | | w+3+2w+w+3+2w=36 | | 3x^2-18=-3x | | 3(x-4)(x-9)=122 | | X+1+5+x=22 | | 2x(2x+y)= | | -3y=-5-4y |